Students Critical Thinking Reviewed from Field-Dependent and Field-Independent on Number Pattern Material - Arigawati, Nur Hijjah; Kusnandi, Kusnandi (Universitas Muhammadiyah Mataram, 2021)
One of the competencies or learning goals in the 2013 curriculum is to promote curiosity, creativity, and the ability to arranging problem to build critical thinking which are necessary for intelligent life. However, in reality, students's critical thinking skills in mathematics are still not satisfactory. Mathematic’ material and critical thinking skills are two things that cannot be separated because mathematics material can be understood through critical thinking which is trained through learning mathematics. Learning number patterns aims to equip students to think critically, analyze, creatively, logically, and systematically. Students' critical thinking skills have related to the existence of cognitive aspects like how to complete a task, make procedures design, and be able to give the right solution in solving problems. This study aims to understand how students of junior high school solve math problems with number pattern material reviewed from students's critical thinking with Field-Dependent (FD) and Field-Independent (FI) cognitive style. The method used in this research is qualitative descriptive method with case study design. From the results of study conducted on 14 students, there were 64% students in the Independent field category and 36% students in the Dependent field category. Of the 2 students, among them taken in the Independent field category, they have high-level critical thinking skills and medium-level critical thinking skills. There are 2 students among those taken in the Dependent field category have critical thinking skills on medium level and low level.